Neonatal intestinal obstruction secondary to Meckel's diverticulum with associated band and ileal stricture: A case report - Priyanka Bamoria; Sheetal Upreti; Eram Nahid; MD. Fahim Ahmad; Prafull Kumar; Simmi K Ratan (EL-Med-Pub, 2024)
Background: Symptomatic Meckel's diverticulum is exceptionally rare in neonates, often presenting as intestinal obstruction or perforation. The differential diagnosis may encompass more prevalent conditions like intestinal atresia, malrotation, or Hirschsprung's disease. Case Presentation: We present a case of a 21-day-old female who presented with intestinal obstruction. Exploratory laparotomy revealed Meckel's diverticulum with a mesodiverticular band causing closed-loop obstruction along with three passable strictures in the ileum. Surgical resection of the affected bowel and the creation of an ileostomy were performed due to bowel ischemia and hemodynamic instability. Conclusion: Early diagnosis and prompt surgical intervention are pivotal in managing neonatal Meckel's diverticulum, reducing risks of bowel necrosis and complications.